EFEKTIVITAS MEDIA VIDEO TERHADAP PERILAKU IBU DALAM PMBA DAN BERAT BADAN ANAK - Hidayaturrahmi; Irianto, Irianto; Narda Widiada, I Gde; Chandradewi , AASP Chandradewi (Media Bina Ilmiah, 2024)
Malnutrition during critical growth can cause stunted growth in children. Lack of awareness of mothers about the importance of proper baby feeding practices is one of the causes. Therefore, educational interventions are needed to improve maternal behavior, utilizing appropriate media such as audio-visual (video) aids. The purpose of this study is to examine the effectiveness of video-based education on maternal behavior in infant feeding (PMBA) and The body weight of children aged 6-23 months in West Monjok District. Video-based PMBA education significantly affects maternal behavior in infant feeding and child weight.